SAP 2000 Validates Deflection in Multilayer Test - Sabaruddin (Graduate Program Magister Manajemen Pendidikan, 2024)
Multilayer testing is one of the non-standard testing methods that has the potential to be developed in the future, so it requires special validation of its results. In this study, validation was carried out using SAP 2000 software, focusing on the calculation of downward curvature that occurs under the concrete layer. The study was conducted on test objects in closed conditions with certain dimensions. The test results showed that there was a difference between the downward curvature values ​​produced from multilayer testing and calculations with SAP 2000. The difference in downward curvature between the two methods was recorded at 15.29%. This difference indicates that more validation is needed to ensure the accuracy of the multilayer testing method in future structural applications.